The social dynamics of Roman imperial imagery - Russell, Amy, 1982-; Hellström, Monica (Cambridge University Press, 2020)
Images relating to imperial power were produced all over the Roman Empire at every social level, and even images created at the centre were constantly remade as they were reproduced, reappropriated, and reinterpreted across the empire. This book employs the language of social dynamics, drawn from economics, sociology, and psychology, to investigate how imperial imagery was embedded in local contexts. Patrons and artists often made use of the universal visual language of empire to navigate their own local hierarchies and relationships, rather than as part of direct communication with the central authorities, and these local interactions were vital in reinforcing this language. The chapters range from large-scale monuments adorned with sculpture and epigraphy to quotidian oil lamps and lead tokens and cover the entire empire from Hispania to Egypt, and from Augustus to the third century CE.